Implementation of Dengue Recurrent Shock Prediction Score in pediatric dengue shock syndrome - Armand Setiady Liwan; I Wayan Gustawan; Eka Gunawijaya; Soetjiningsih Soetjiningsih; Ketut Ariawati; I Nyoman Budi Hartawan (Paediatrica Indonesiana, 2020)
Background Global morbidities due to dengue viral infection increase yearly. The pediatric mortality rate from dengue shock syndrome (DSS) remains high. Early identification of the risk of recurrent shock may serve to increase awareness and reduce mortality. The Dengue Recurrent Shock Prediction Score (DRSPS) is a tool to predict recurrent shock in children with DSS, but the optimal cut-off point in our population is still unknown. Objective To assess the validity of the DRSPS by determining the optimal cut-off point that can be used in Indonesia Methods This cross-sectional prospective study was done at Sanglah Hospital, Denpasar, Bali, from January 2019. Risk of reccurent shock were classify based on DRSPS in all DSS patient, and they were observed whether they will experienced recurrent shock or not. Results Of 56 children with DSS, 27 subjects had recurrent shock and 29 subjects did not. The optimal DRSPS cut-off point was -189.9 for predicting recurrent shock, with 87.4% area under the curve (AUC), 81.5% sensitivity and 82.8% specificity. Conclusion The optimal cut-off point of DRSPS was -189.9 and it has good validity. The results of this study are expected not only to be used as the basis for further study, but to increase physician awareness in treating DSS patients.